Dressing after stroke - Walker, Marion Fraser (1991)
The literature available indicates that dressing difficulties after stroke are common and persistent. Previous studies have documented dressing ability but none have investigated each individual component of the dressing process using a detailed dressing assessment suitable for stroke patients.